Theology Before and After Bishop Robinson’s Honest to God (1963) (Journal for the Study of Religion)
Bishop John Robinson’s Honest to God (1963) may be judged as a bombshell that blew the roof off the church, not because it introduced original thinking, but because it brought to unsuspecting people in the pews some knowledge of the developments that had been taking place for quite some time in academic theology. It initiated the turbulent sixties from which time onwards the slow decline in church allegiance began to accelerate in the Western world. The thought of Dietrich Bonhoeffer, Rudolf Bultmann and Paul Tillich, which Robinson summarized in his book, were themselves simply the twentieth century version of the radical changes in theology made necessary by the advent of the post-Enlightenment world, and which had been set in motion in rather different ways at the beginning of the nineteenth century by the philosopher Georg Wilhelm Friedrich Hegel, and the theologian Friedrich Schleiermacher. Since the Enlightenment brought to humans the freedom to think for themselves – Bonhoeffer labelled this phenomenon ‘Humanity’s coming of age’ – so the theological enterprise gradually changed from being the exposition of divinely revealed dogmas to the human exploration of religious experience. In retrospect, Robinson’s book is to be judged a significant marker in a process of ever-changing theological thought.